Potency of Indonesian Herbal Compounds as Human Flavin Containing Monooxygenase 3 Inhibitor for Atherosclerosis Prevention - Fadhila Balqis Nurfitria; RAJ Sri Wulandari; Dono Indarto (Nexus Kedokteran Translasional, 2017)
Introduction: Atherosclerosis complication in the cardiovascular system has been one of the biggest medical problems in recent years and the definitive treatment has not been found. Trimethylamine-N-oxide (TMAO) is a catalytic product of Flavin-Containing Monooxydase (FMO) 3 enzyme and might act as a predispostion factor for atherosclerosis. Indonesia has many herbal plants which can potentially be developed into antiatherosclerosis drug. This was an initial study of drug development which aimed to identify FMO3 inhibitors from Indonesian herbal plants by using molecular docking. Methods: It was a bioinformatics study which utilized all herbal compounds recorded in HerbalDB, had three dimentional structure, and met the criteria for Lipinski's rule of five. Methimazole was used as a standard ligand and hFMO model was determined using FMO protein template from Methylophaga aminisulfidivorans. Herbal compounds were molecularly docked with hFMO3 models using AutodockVina 1.1.2. PyMOL 1.7 dan Chimera 1.10rc were used for visualization of docking results. Binding affinity, binding site, and Lipinski's rule of five criterias were used to determine hFMO3 inhibitor candidates of herbal compounds. Results: Methimazole bound to the hFMO3 model at Asn194 with binding energy average of -3.8 kcal/mol. Droserone, vanillic acid, (s)-(+) abscisic acid, and sebacic acid had lower binding energy, had similar binding site, and had the best drug like property, compared with methimazole. Conclusion: Droserone, vanillic acid, (s)-(+) absicic acid, and sebacic acid become the potential candidates of hFMO3 inhibitor in silico. A future study using flexible ligand and flexible receptor docking methods is needed to get more accurate results. Keywords: Atherosclerosis, Molecular Docking, FMO3 inhibitor, Indonesian Herbal Plants